Utilization of Lactobacillus cells as a probiotic in chewing gum against multi-drug-resistant pathogens associated with gingival inflammation - Nooruldeen, Tuqa Sameer; Luti , Khalid Jaber Kadhum (Iraqi Journal of Science, 2026)
This study was Conceived to choose an appropriate isolate of Lactobacillus sp. To use it as a probiotic in chewing gum for the Prophylaxis of gingivitis. Due to the above reason, 20 Lactobacillus isolates were collected from various sources and then primarily enrolled in a screening program to assess their activities of antagonism against two oral pathogens, Streptococcus pluranimalium and Staphylococcus aureus. Twenty Lactobacillus isolates were selected from the initial screening based on their efficacy to suppress the growth of the two chosen indicators which was then followed by another step of secondary screening to detect their production of the high amount of bacteriocin and their effectiveness. The key findings show, that the isolate of Lactobacillus rhamnosus T was chosen it’s the producing isolate of the highest bacteriocin. Then, several in vitro experiments were run to determine the characteristics of Lactobacillus rhamnosus T, mostly, its biosafety considerations and its validity for acting as a successful probiotic which all revealed the suitability of this isolate to use as a probiotic. Five types of natural and artificial gums were tested to select one that can be utilized in producing chewing gum containing Lactobacillus rhamnosus T cells which were encapsulated before integrating into the sterile prepared chewing gum. Based on the results, the chewing gum base, water Iraqi gum, xanthan gum [XG], and Arabic gum showed good viability based on the high number of colonies revealed on the MRS agar after 21 days whereas the minimum viability result was gained for the Frankincense.